A study of disability and perceived stress in patients of anxiety disorders - Dharamveer Chaudhary; Bharat N Panchal; Ashok U Vala; Imran J Ratnani; Sneha Vadher (Telangana Journal of Psychiatry, 2017)
Introduction: Patients of anxiety disorders have substantial work disability, social impairment, perceived stress and lower life satisfaction. Aims: We assessed perceived stress level in various anxiety disorders and examined association of perceived stress with severity of anxiety and disability. Materials & Methods: This was an observational, single center, cross sectional, interview based study of 150 patients attending Psychiatry OPD of tertiary care hospital. Every consenting participant was interviewed by Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM 5) for diagnosis of anxiety disorder and those qualifying for the diagnosis were assessed for severity of anxiety disorder by Hamilton Anxiety Rating Scale (HAM-A), perceived stress was measured by the perceived Stress Scale (PSS) and disability by World Health Organization Disability Assessment Schedule 2.0(WHODAS 2.0). The patients were further assessed for demographic details. The statistical analysis was done with graphpad instat version 3.06 Proportion of participants were compared by using chi-square test while score of PSS, HAM-A and WHODAS2.0 were compared using Kruskal-Wallis test or Mann-Whitney test. Correlation between severity of anxiety, perceived stress level and severity of disability was assessed by Spearman’s rank correlation. A p value of <0.05 was considered statistically significant. Results: We found participants with high perceived stress level were having more anxiety symptoms (p<0.0001) and vice a versa (p value <0.0001). We found that participants having more anxiety symptoms are likely to have significant disability in all domains of WHODAS 2.0 (p<0.0001). Conclusion: Participants with higher perceived stress have severe anxiety symptoms and more disability.